Effect of light level and fertillizer sources on growth and quality of kaduk (Piper sarmentosum) - Nur Halimah Saiful Anwar
This study was carried out to investigate the growth and quality of Piper sarmentosum as affected by light levels and sources of fertilizer. P. sarmentosum was propagated using stem cutting and planted in polybag 25.4cm x 30.5cm. The experiment was laid out in split plot design with 3 replications. The main plot was light levels consisting of 30%, 70% and 100% while the subplot was sources of fertilizer namely, vermicompost, EFB compost, EFB biochar and NPK 15:15:15. Data collected for plant growth analysis at 2 weeks interval was total dry mass, total leaf area and specific leaf area. For physiological analysis, photosynthetic rate, stomatal conductance and chlorophyll content was taken at week 4 and 8 after transplant. Data for nutrient and phenolic contents were analysed at 10 WAT. All the data were analysed by using analysis of variance (ANOVA). Piper sarmentosum grown under 100% light intensity and fertilized with NPK 15:15:15 showed better growth performance and physiological activities. Among organic fertilizers, vermicompost gave better result by increasing photosynthetic rate, stomatal conductance, total chlorophyll content and total phenolics acid compared to other organic sources. Results suggested that vermicompost could be the most potential source of fertilizer to replace inorganic fertilizer in producing quality of P. sarmentosum.